Monitoring COVID-19 Impacts on Firms in Ethiopia : Does the COVID-19 Pandemic Affect Women-Owned Firms Differently - Abebe, Girum (World Bank, Washington, DC, 2020)
As COVID-19 continues to disrupt the Ethiopian economy, a major concern is that the pre-existing gendered challenges facing women entrepreneurs, in access to capital and hired labor, for example, will worsen, further undermining the survival and performance of women-owned firms. However, very little data exist to monitor the gender differences in impacts brought about by the COVID-19 pandemic. Therefore, in April 2020, the World Bank launched a high-frequency phone survey (HFPS-F) of a random sample of firms in Addis Ababa to collect detailed information on firm operations, hiring and firing, and expectations of future operations and labor demand. The analysis that follows draws on the three rounds of the HFPS-F survey implemented between April 15 and June 18, 2020, consisting of a balanced panel of 454 firms from Addis Ababa.